Comentarios a la legislación y a la jurisprudencia del contrato de arrendamiento en el Perú a los 40 años de vigencia del Código Civil - Villota Cerna, Marco (2024)
This article analyzes the regulation of the lease contract in the Civil Code from a jurisprudence and comparative law point of view to suggest some regulatory changes or interpretation criteria after 40 years of validity of the Peruvian Civil Code. The article analyzes the relationship between the lease and the right of possession to distinguish it from the real right of use and; usufruct, deals with the lease subcontract to delimit the responsibilities of the subtenant and, above all, focuses on the issue of the duration of the lease contract, regarding the discussion whether the tenant with an expired contract has the status of precarious occupant. Finally, it analyzes the various forms of conclusion of thep;lease contract, the causes of the eviction process and the various types of process, in order to streamline the eviction process.